SIRT7, H3K18ac, and ELK4 Immunohistochemical Expression in Hepatocellular Carcinoma - Lee, Hye Seung (J Pathol Transl Med, 2016)
BACKGROUND: SIRT7 is one of the histone deacetylases and is NAD-dependent. It forms a complex with ETS-like transcription factor 4 (ELK4), which deacetylates H3K18ac and works as a transcriptional suppressor. Overexpression of SIRT7 and deacetylation of H3K18ac have been shown to be associated with aggressive clinical behavior in some cancers, including hepatocellular carcinoma (HCC). The present study investigated the immunohistochemical expression of SIRT7, H3K18ac, and ELK4 in hepatocellular carcinoma. METHODS: A total of 278 HCC patients were enrolled in this study. Tissue microarray blocks were made from existing paraffin-embedded blocks. Immunohistochemical expressions of SIRT7, H3K18ac and ELK4 were scored and analyzed. RESULTS: High SIRT7 (p = .034), high H3K18ac (p = .001), and low ELK4 (p = .021) groups were associated with poor outcomes. Age < 65 years (p = .028), tumor size ≥ 5 cm (p = .001), presence of vascular emboli (p = .003), involvement of surgical margin (p = .001), and high American Joint Committee on Cancer stage (III&V) (p < .001) were correlated with worse prognoses. In multivariate analysis, H3K18ac (p = .001) and ELK4 (p = .015) were the significant independent prognostic factors. CONCLUSIONS: High SIRT7 expression with poor overall survival implies that deacetylation of H3K18ac contributes to progression of HCC. High H3K18ac expression with poor prognosis is predicted due to a compensation mechanism. In addition, high ELK4 expression with good prognosis suggests another role of ELK4 as a tumor suppressor beyond SIRT7’s helper. In conclusion, we could assume that the H3K18ac deacetylation pathway is influenced by many other factors.